2017
DOI: 10.29252/johe.6.2.61
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal and other performance related disorders in South African undergraduate music students

Abstract: Received: March 2017, Accepted: July 2017Background: Performance related musculoskeletal and associated health issues are prominent amongst musicians. The aim of this study was to explore self-reported musculoskeletal and related health issues in undergraduate music students. A further goal was to ascertain how these problems impact students' learning and playing their instruments. Materials and Methods: A longitudinal mixed method study was done over a period of three years with 145 undergraduate music studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In the literature, posture, repetitive movements, time spent on studying, time spent on the computer and lifting of both equipment and patients were found to have positive associations or relationships with MSDs. Studies by Panebianco (2017), Moodley and Naidoo (2015) and Morais et al (2019) confirmed the association between the above factors and MSD prevalence. High frequencies of postural and lifting challenges were recorded in the present study, corroborating the above findings.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In the literature, posture, repetitive movements, time spent on studying, time spent on the computer and lifting of both equipment and patients were found to have positive associations or relationships with MSDs. Studies by Panebianco (2017), Moodley and Naidoo (2015) and Morais et al (2019) confirmed the association between the above factors and MSD prevalence. High frequencies of postural and lifting challenges were recorded in the present study, corroborating the above findings.…”
Section: Discussionmentioning
confidence: 79%
“…The relatively high MSDs prevalence amongst nursing professionals has been discussed as a norm by Tinubu et al (2010) and Ribeiro et al (2017). Abledu and Offei (2015) found a comparatively lower prevalence rate amongst nursing students at a Ghanaian college (70.1%), whilst Panebianco (2017) found an 83% prevalence of MSD amongst music students at the University of Pretoria. Almhdawi and Choobineh (2017) asserted that the worldwide MSD prevalence is 67.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on the occupational health problems of South African undergraduate students has indicated that their health-promoting behaviours, and in particular the healthpromoting behaviours of music students (Panebianco-Warrens et al, 2015;Panebianco 2017), are comparable with those identified in international studies (Ajidahun & Phillips 2013;Barnes et al, 2011). Performing artists in South Africa lack awareness of medical issues (Devroop, 2014), andRennie-Salonen andDe Villiers (2016) argue that tertiary training for performance in South Africa should include Performing Arts Medicine.…”
Section: Associations Between Personality General Self-efficacy and H...mentioning
confidence: 87%
“…Investigations of the physiological and psychological risks associated with the lives of professional classical musicians have been well covered in the literature (Ackermann et al, 2014; Kenny et al, 2014; Kok et al, 2016; Vaag et al, 2016), and reveal a high prevalence of performance-related musculoskeletal disorders (Gasenzer et al, 2017; Kaufman-Cohen & Ratzon, 2011, Leaver et al, 2011; Stanhope et al, 2019) and music performance anxiety (MPA) (Cohen & Bodner, 2019a; Fishbein et al, 1988; Kenny et al, 2014, 2018). Of even more concern is the evidence that many younger musicians, including music students, also suffer from pain and performance-related musculoskeletal disorders (Ackermann & Driscoll, 2013; Ballenberger et al, 2018; Ginsborg et al, 2009; Panebianco, 2017; Spahn et al, 2017) and MPA (Biasutti & Concina, 2014; Cohen & Bodner, 2019b; Papageorgi et al, 2013; Osborne & McPherson, 2018). The high prevalence of these physiological and psychological risks to health and wellbeing among musicians has led to investigations of health-promoting behaviours among music students (Araújo et al, 2017; Ballenberger et al, 2018; Ginsborg et al, 2009; Matei et al, 2018; Panebianco-Warrens et al, 2015; Spahn et al, 2004).…”
Section: Introductionmentioning
confidence: 99%